Less Evidence, Better Knowledge - Ehrenberg, Kenneth (McGill Law Journal / Revue de droit de McGill, 2015)
In his 1827 work Rationale of Judicial Evidence, Jeremy Bentham famously argued against exclusionary rules such as hearsay, preferring a policy of “universal admissibility” unless the declarant is easily available. Bentham’s claim that all relevant evidence should be considered with appropriate instructions to fact finders has been particularly influential among judges, culminating in the “principled approach” to hearsay in Canada articulated in R. v. Khelawon. Furthermore, many scholars attack Bentham’s argument only for ignoring the realities of juror bias, admitting universal admissibility would be the best policy for an ideal jury. This article uses the theory of epistemic contextualism to justify the exclusion of otherwise relevant evidence, and even reliable hearsay, on the basis of preventing shifts in the epistemic context. Epistemic contextualism holds that the justification standards of knowledge attributions change according to the contexts in which the attributions are made. Hearsay and other kinds of information the assessment of which rely upon fact finders’ more common epistemic capabilities push the epistemic context of the trial toward one of more relaxed epistemic standards. The exclusion of hearsay helps to maintain a relatively high standards context hitched to the standard of proof for the case and to prevent shifts that threaten to try defendants with inconsistent standards.